Selective Electrochemical Determination of Dopamine with Molecularly Imprinted Poly(Carbazole‐co‐Aniline) Electrode Decorated with Gold Nanoparticles. Issue 5 (23rd December 2019) - Sağlam, Şener; Arman, Aysu; Üzer, Ayşem; Ustamehmetoğlu, Belkıs; Sezer, Esma; Apak, Reşat
Abstract: Dopamine (DA) is a significant neurotransmitter in the central nervous system, coexisting with uric acid (UA) and ascorbic acid (AA). UA and AA are easily oxidizable compounds having potentials close to that of DA for electrochemical analysis, resulting in overlapping voltammetric response. In this work, a novel molecularly imprinted (MI) electrochemical sensor was proposed for selective determination of DA (in the presence of up to 80‐fold excess of UA and AA), relying on gold nanoparticles (Aunano )‐decorated glassy carbon (GC) electrode coated with poly(carbazole (Cz)‐ co ‐aniline (ANI)) copolymer film incorporating DA as template (DA imprinted‐GC/P(Cz‐co‐ANI)‐Aunano electrode, DA‐MIP‐Aunano electrode). The DA recognizing sensor electrode showed great electroactivity for analyte oxidation in 0.2 mol L −1 pH 7 phosphate buffer. Square wave voltammetry (SWV) was performed within 10 −4 –10 −5  mol L −1 of DA, of which the oxidation peak potential was observed at 0.16 V. The limit of detection (LOD) and limit of quantification (LOQ) were 2.0×10 −6 and 6.7×10 −6  mol L −1, respectively. Binary and ternary synthetic mixtures of DA‐UA, DA‐AA and DA‐UA‐AA yielded excellent recoveries for DA. Additionally, DA was quantitatively recovered from a real sample of bovine serum spiked with DA, and determined in concentrated dopamine injection solution. The developed SWV method was statistically validated against a literature potentiodynamic method using a caffeic acid modified‐GC electrode. Abstract :